Pharmacokinetics and Bioequivalence of Two Fixed-Dose Combination Tablets of Valsartan/Amlodipine (80/5 Mg) in Healthy Chinese Subjects - Tian M; Huang J; Chen Y; Jin Q; Jiang H; Shi C; Mei J; Xu M; Yu X; Yang S (Drug Design, Development and Therapy)
Mengli Tian,1 Jinlong Huang,2 Yingrong Chen,1 Qiuyue Jin,1 Hong Jiang,2 Cunyuan Shi,2 Jue Mei,1 Min Xu,1 Xiang Yu,1 Shuixin Yang1 1Clinical Trial Center, Huzhou Central Hospital, Fifth School of Clinical Medicine of Zhejiang Chinese Medical University, Huzhou, 313000, People’s Republic of China; 2Zhejiang Jianfeng Pharmaceutical Co Ltd., Jinhua, 321025, People’s Republic of ChinaCorrespondence: Shuixin Yang, Clinical Trial Center, Huzhou Central Hospital, Fifth School of Clinical Medicine of Zhejiang Chinese Medical University, 1558, North Third Ring Road, Huzhou, 313000, People’s Republic of China, Tel +86-0572-2978254, Email ysx@hzhospital.comPurpose: The study aimed to investigate the pharmacokinetics and bioequivalence of coformulations of valsartan and amlodipine in healthy Chinese subjects under both fasting and fed conditions.Methods: The research was conducted under both fasting and fed studies and employed a single-center, randomized, open-label, single-dose, three-period design with partial-repeat and crossover elements. A total of 71 healthy Chinese adult participants were included under fasting (n = 36) and fed (n = 35) conditions. The subjects were orally administered valsartan/amlodipine tablets (80/5 mg) per cycle either as the test (T) or reference (R) formulation. The washout period was 14 days. Plasma concentrations of valsartan and amlodipine were determined using ultrahigh-performance liquid chromatography–tandem mass spectrometry (UPLC-MS/MS), and the noncompartmental analysis method was used for estimating the pharmacokinetic parameters.Results: Under fasting conditions, the within-subject standard deviations (Swr) of maximum plasma concentration (Cmax), area under the concentration–time curve from time 0 to the time of the last-measurable plasma concentration (AUC0−t), and area under the concentration–time curve from time 0 extrapolated to infinity (AUC0−∞) for valsartan were calculated to be ≥ 0.294 and evaluated by the reference-scaled average bioequivalence (RSABE) method. The point estimates of the geometric mean ratios (GMRs) of Cmax, AUC0−t, and AUC0−∞ for valsartan were 1.0805, 1.0991, and 1.1015 respectively, and the critical bounds were all less than 0. The Swr of Cmax, AUC0−t, and AUC0−∞ for amlodipine were all < 0.294, and the 90% confidence intervals (CIs) of the GMRs fell within the bioequivalence range, as evaluated by the average bioequivalence (ABE) method. Under the fed condition, the Swr of Cmax, AUC0−t, and AUC0−∞ were all < 0.294 for both valsartan and amlodipine; the ABE method was therefore employed for the evaluation of bioequivalence, and the 90% CIs of the GMRs fell within the bioequivalence range. All the observed adverse events were mild and transient.Conclusion: The two formulations of valsartan/amlodipine (80/5 mg) tablets were bioequivalent and safe.Keywords: valsartan, amlodipine, bioequivalence, pharmacokinetics, safety